Optimal annual solar PV penetration for improved voltage regulation and power loss reduction under uncertainty conditions - Ba-swaimi, Saleh; Verayiah, Renuga; Ramachandaramurthy, Vigna K.; Binajjaj, Saeed Ali; Padmanaban, Sanjeevikumar (Institute of Advanced Engineering and Science, 2025)
Given their technological, economic, and environmental advantages, the widespread adoption of renewable distributed generators (RDGs) in distribution systems (DSs) is becoming more prevalent. However, Solar photovoltaic distributed generators (PV-DGs) face the challenge of intermittent behavior, which results in power output fluctuations and increased grid uncertainty. Therefore, addressing these uncertainties is crucial when determining their optimal allocation. The proposed method considers uncertainties related to both load demand and solar irradiation. The model is formulated as a stochastic mixed-integer nonlinear optimization problem, which is solved using the whale optimization algorithm (WOA). The standard IEEE 33-bus system is used to validate the proposed approach, and demand variations are modeled based on the IEEE reliability test system (IEEE-RTS). The objective is to simultaneously minimize total expected voltage deviation, real power loss, and reactive power loss while increasing solar PV penetration. The technique for order of preference by similarity to the ideal solution (TOPSIS) is applied to select the best solution. Simulated results indicate significant improvements: a 19.39% reduction in voltage deviation, an 18.42% decrease in total real power loss, and an 18.53% reduction in reactive power loss compared to the base case. Additionally, the model accommodates a total of 3.206625 MW of solar PV power in the DS.